TANTANGAN PENDIDIKAN AGAMA ISLAM DI ERA GLOBALISASI: TELAAH KONSEPTUAL TERHADAP PENGUATAN KARAKTER DAN IDENTITAS KEISLAMAN - Ahmad Habiburrahman; Dinda Nurul Kholifah; Muhammad Rafi; Surya Abdul Karim; Nur Azizah; Rodianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to analyze the challenges of Islamic Religious Education in the era of globalization and to formulate strategic implications for strengthening students’ character and Islamic identity. This study employs a qualitative approach using library research. The data were collected from books, journal articles, and previous studies relevant to globalization, Islamic education, character education, digital literacy, and youth identity. The data were analyzed through reduction, thematic categorization, interpretation, and conclusion drawing. The findings show that the main challenges of Islamic Religious Education in the globalization era include the development of science and technology, democratization of education, moral decadence, the rise of secularism and liberalism, and the identity crisis among young people. These challenges require Islamic Religious Education to function not merely as a transmission of religious knowledge, but also as an instrument for character building, digital literacy strengthening, and spiritual development. This article emphasizes the need for adaptive, moderate, and contextual Islamic education learning innovations so that students can face globalization without losing their moral values and Islamic identity.